The role of factor substitution and technical progress in China's great expansion - Ana-Simona Manu; Peter McAdam; Alpo Willman (European Central Bank (ECB), 2018)
We offer a macroeconomic assessment of China's Reform Period, highlighting several neglected channels underlining its great expansion. Estimating the supply side of the post-Reform economy reveals the relatively high (above unity) value of the elasticity of factor substitution and the time-varying pattern of factor-saving technical change. The latter we relate to trade, human capital and reallocation factors. We then demonstrate how, in addition to factor accumulation and technical progress, the above-unity elasticity of substitution can be a source of growth (the 'de La Grandville hypothesis'). We then draw upon our estimated framework to rationalize China's high and rising savings ratio as well as the dynamic nature of its convergence path.
Keywords: D24; E13; O11; 330; China; Reform Period; Growth; TFP; Factor Substitution; de La Grandville hypothesis; Optimal Savings